PERAN HUMAS KAB. BOYOLALI DALAM MENUNJANG KEBERHASILAN CITY BRANDING KABUPATEN BOYOLALI - Della Candra Novitasari Putri Utami; Yenni Sri Utami; Sigit Tripambudi (Jurnal Paradigma, 2017)
Boyolali smart city is a leading development priorities Boyolali District Government, the concept of smart cities are connected with telecommunication base applied by eliminating the use of paper instead implement a network program for the bureaucratic process. PR Boyolali District Government has a role as a communicator and funnel regents as a bridge to inform all policies and activities that have been made by the government. The purpose of this study was to determine the smart city branding, the role of public relations in the smart city, and the impact of the application of smart city in Boyolali. The theory used is the system theory, this theory provides a theoretical foundation for analyzing the role of public relations that organizational life is very dependent on building and maintaining good relationships within the organization and the environment. This type of research is descriptive qualitative research approach, this study used data collection techniques in-depth interviews (in-depth interviewing), observation, literature and documentation. The results of this study, PR of Boyolali District Government has an important role in supporting the success of smart city in Boyolali, PR role in designing application programs, publicizing and disseminating the smart city program to local governments and communities. Branding smart city supported by a program of technology applications based communications that are formulated into the Green Public Procurement as an example P-Email and SIMANTAP to support effective performance of the government and community to facilitate services enabling faster, precise, effective, public welfare, and promote Boyolali. The application of smart city has some resistance, but a positive impact on society and the government.